Building a Resilient Immune System: The Role of Nutrition and a Healthy Lifestyle - Nayla Alator (Journal of Nutrition and Health Care, 2024)
A strong immune system is the main defense against various health threats. This research aims to investigate the role of nutrition and a healthy lifestyle in building and maintaining a strong immune system. This prospective cohort study involved 500 healthy participants aged 18-65 years who were followed for 12 months, and divided into four groups: control, nutritional intervention, lifestyle intervention, and combination intervention. Nutritional interventions include diets rich in antioxidants and immune-supporting nutrients, while lifestyle interventions include structured exercise programs, stress management, and improved sleep quality. Immune parameters measured include the number and activity of NK cells, CD4+/CD8+ ratio, cytokine levels, and antibody response to vaccination. The results show a significant synergistic effect between optimal nutrition and a healthy lifestyle in improving immune function. The combination intervention group showed the greatest increase in NK cell numbers (27.3%, p<0.001), decreased CRP levels (22.3%, p<0.01), and increased salivary IgA (15.7%, p<0.05). Multivariate regression analysis identified vitamin D intake, moderate-intensity physical activity, sleep quality, and stress levels as major predictors of immune function. The study also revealed a significant increase in antibody response to influenza vaccine in the lifestyle intervention group (23.4%, p<0.001). These findings have broad implications for clinical practice and public health policy, supporting a holistic approach to improving immune health. Although long-term research is needed to assess the impact on disease incidence, this study confirms that the combination of proper nutrition and a healthy lifestyle is an effective strategy for building a resilient immune system, potentially improving the overall health and well-being of society.